Al-Muḍārabah Min Wujhat Naẓr al-fiqh wa-Tajribat Bank al-Syarī'ah - Abd Salam Arief (Al-Jami'ah Research Centre, 2004)
In Indonesian society, mudhārabah is one of sharīah economics systems that have been performed since long time ago in rural society. One example of mudhārabah is that landowners give the authority to other people to manage their lands and to share their crops. In fact, the prophet Muhammad has also done in his time of a such kind mudhārabah system in his society. In doing so, two parts are involved, the investor (shāhih al māl) and the manager of the land (al-mudhārib). Nowadays, mudbārabah is an Islamic economics system that is offered by sharīah banks to attract more customers. In applying this system, mudhārabah can be seen in two ways, as a system and as a product. Mudhārabah as a system is when it is used as guidance by a bank in its transactions. i,e., Partnerships agreement between the owner of the capital and the manager of a business is based on outcomes sharing. Mudbārabah as a product was applied in two ways in sharīah banks, i.e. the bank as the owner of the capital and the bank as the manager of a business. This article illustrates the way that nudhārabah is applied in sharīah banks in the perspective of fiqh.